A greener seawater desalination method by direct-contact spray evaporation and condensation (DCSEC): Experiments. (October 2020) - Alrowais, Raid; Qian, Chen; Burhan, Muhammad; Ybyraiymkul, Doskhan; Shahzad, Muhammad Wakil; Ng, Kim Choon
Highlights: A greener seawater desalination method for sustainable future. Simple hollow vessel design, no heat transfer interfaces, exploits liquid flashing. Robust operation, lowest CAPEX and OPEX amongst all practical desalination methods. Resilient to high salinity, feed temperature with micro-bubble enhanced flashing. Abstract: Owing to the high specific energy consumption of conventional seawater desalination methods available hitherto, there is much motivation for designing greener desalination processes. As a greener desalination process, it should consume lower top-brine temperatures for the seawater feed as well as minimum chemical use for brine treatment. In this paper, a direct-contact spray-assisted evaporation and condensation (DCSEC) is presented that addresses the above-mentioned requirements of greener desalination. We have tested both the single-stage and multi-stage configurations of DCSEC process with seawater (3.5% by weight salinity) from Red Sea. The performance of the system was investigated for a feed flow rate of 6 L/minute when the evaporator chamber temperature was varied from 38 °C to 60 °C. From the experiments, maximum distillate production of 31 L/hr m 3 was recorded at 60 °C feed temperature for a single-stage configuration. To further enhance the distillate production of DCSEC, an innovative micro/nano-bubbles (M/NBs) generator device is incorporated in the feed supply system which resulted in 34% increase in potable water production at the corresponding inlet feed temperatures.